2012
DOI: 10.5489/cuaj.11202
|View full text |Cite
|
Sign up to set email alerts
|

The association between renal tumour scoring systems and ischemia time during open partial nephrectomy

Abstract: Preoperative patient characteristics (age, gender, preoperative renal function, diabetes, hypertension, smoking history, heart disease) and ischemia time were abstracted from medical records. Preoperative computed tomography (CT) images were reviewed and tumours were characterized using three scoring systems: (1) R.E.N.A.L. nephrometry score (radius, exophytic/endophytic properties, nearness of tumour to the collecting system or sinus in millimetres, anterior/posterior, location relative to polar lines); (2) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
2
11
0
2
Order By: Relevance
“…No significant correlations were found between any of the subscales and percent change in eGFR from baseline. Our results, corroborated by the heterogeneity of outcomes from other studies [9 10,11,12…”
Section: Discussionsupporting
confidence: 89%
“…No significant correlations were found between any of the subscales and percent change in eGFR from baseline. Our results, corroborated by the heterogeneity of outcomes from other studies [9 10,11,12…”
Section: Discussionsupporting
confidence: 89%
“…10 In their OPN series, Lavallee and colleagues found that several parameters of tumour complexity positive correlated with warm ischemic time. 19 However, Mufarrij and colleagues demonstrated that nephrometry-graded tumour complexity was not related to warm ischemic time for 92 patients who underwent RPN. 20 Their interpretation was that since their series was based on the skills of a highly experienced laparoscopic and robotic surgeons, differences between simple and complex cases were too minuscule to detect.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this sometimes limits their abilities to effectively reflect the surgical complexity and predict the risk of surgical complications. We found that each system's ability to predict clinical outcomes of PN has been inconsistent between studies . Furthermore, morphological descriptors, such as the exophytic rate and anterior/posterior descriptor in the RENAL nephrometry scoring system and the anterior or posterior face, longitudinal, and rim tumor location, and exophytic rate in the PADUA scoring system, appear clinically irrelevant for predicting clinical outcomes of PN …”
Section: Introductionmentioning
confidence: 91%